Impact of COVID-19 Pandemic on the Italian Humanitarian Congenital Cardiac Surgery Activity: What No One Tells You - Giamberti, Alessandro; Caldaroni, Federica; Varrica, Alessandro; Pace Napoleone, Carlo; Marianeschi, Stefano Maria; Uricchio, Nicola; Vanini, Vittorio; Santoro, Francesco; Luciani, Giovanni Battista; Stellin, Giovanni; Gargiulo, Gaetano; Murzi, Bruno; et al. (Frontiers in Cardiovascular Medicine, 2021)
More than 4 millions of children with congenital heart disease (CHD) are waiting for cardiac surgery around the world. Few of these patients are treated only thanks to the support of many non-governmental organizations (NGOs). Starting in December 2019, the so-called coronavirus disease 2019 (COVID-19) has rapidly become a worldwide pandemic and has dramatically impacted on all the international humanitarian activities for congenital heart disease. We analyzed data from all the Italian congenital cardiac surgery centers with the aim to quantify the impact of the pandemic on their charities. Fifteen Italian centers participated in the study and contributed to data collection. We analyzed and compared data regarding humanitarian activities carried out abroad and on site from two periods: year 2019 (pre-COVID-19) and year 2020 (COVID-19 pandemic). In 2019, 53 international missions were carried out by Italian congenital cardiac surgeons, resulting in the treatment of 471 CHD patients. In the same period 11 Italian cardiac centers operated on 251 foreign patients in Italy. In 2020, the pandemic led to a reduction of this activity by 96% for the surgery performed overseas and 86% for the interventions carried out in Italy. In conclusion our study shows the important quantitative impact of the pandemic on the Italian humanitarian cardiac surgical activity overseas and in Italy. This shocking result highlights the failure of the systems adopted so far to solve the problem of CHD in developing countries.